2019
DOI: 10.1016/j.cdtm.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of Fusobacterium nucleatum in colorectal cancer: from carcinogenesis to clinical management

Abstract: Colorectal cancer (CRC) is a common malignant tumor that affects people worldwide. Metagenomic analyses have shown an enrichment of Fusobacterium nucleatum (F. nucleatum) in colorectal carcinoma tissue; many studies have indicated that F. nucleatum is closely related to the colorectal carcinogenesis. In this review, we provide the latest information to reveal the related molecular mechanisms. The known virulence factors of F. nucleatum promote adhesion to intestinal epithelial cells via FadA and Fap2. Besides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 79 publications
1
81
0
Order By: Relevance
“…The main functions performed by gut microbiota are trophic (i.e., the control of epithelial cell proliferation and differentiation), metabolic (i.e., the fermentation of indigestible food components into absorbable metabolites), and protective (i.e., the out-competition of pathogens) that are essential to maintain human health status. As the gut microbiota has a well-established role in host homeostasis, several highly prevalent gastrointestinal diseases, including cancer, have been associated with dysbiosis in microbiota composition [33].…”
Section: Oral and Intestinal Microbiota And Colorectal Cancermentioning
confidence: 99%
“…The main functions performed by gut microbiota are trophic (i.e., the control of epithelial cell proliferation and differentiation), metabolic (i.e., the fermentation of indigestible food components into absorbable metabolites), and protective (i.e., the out-competition of pathogens) that are essential to maintain human health status. As the gut microbiota has a well-established role in host homeostasis, several highly prevalent gastrointestinal diseases, including cancer, have been associated with dysbiosis in microbiota composition [33].…”
Section: Oral and Intestinal Microbiota And Colorectal Cancermentioning
confidence: 99%
“…There is also cumulative evidence that suggests a link between gut, colorectal adenoma, CRC, and some specific species such as Fusobacterium nucleatum [ 144 , 145 ].…”
Section: Gut Microbiota and Their Metabolites In Adenomatous Colonmentioning
confidence: 99%
“…For example, it has been reported that the enterotoxigenic Bacteroides fragilis contribute to colon carcinogenesis by producing toxins [ 11 ]. Together with numerous potential carcinogenic intestinal microorganisms, Fusobacterium nucleatum ( F. nucleatum ) has been reported to be a contributing factor to CRC progression based on its presence in CRC specimens [ 12 , 13 , 14 ]. The importance of F. nucleatum in CRC is further supported by reports that it increases the chemoresistance of colon cancer via modulating autophagy and enhances the proliferation and tumor development of CRC by activating Toll-like receptor 4 (TLR4) signaling [ 9 ].…”
Section: Introductionmentioning
confidence: 99%